Decision Support System For Submitting Work Leave Using The Vikor Method - Muhammad Rivaldi Prastowo; Yani Maulita; Suci Ramadani (International Journal of Health Engineering and Technology, 2022)
Human resources have an important role in an office, namely as the spearhead for carrying out the organization's activities, because after all the progress and success of a company cannot be separated from the role and capabilities of good human resources. This study aims to determine the effect of work motivation (X1) and work ability (X2) variables partially and simultaneously on employee performance (Y). This type of research is explanatory research with a quantitative approach and is carried out using the genetic method. Genetics is a search technique that in computer science to find approximate solutions for optimization and Genetic search problems are particularly applied as computer simulations in which a population of abstract representations (called chromosomes) of candidate solutions (called individuals) to an optimization problem develops into a solution. - a better solution. This research was conducted on 40 permanent employees of the Binjai City Regional Civil Service Agency.